PENGARUH KOMITE AUDIT DAN AUDIT EKSTERNAL TERHADAP MANAJEMEN LABA - Windasari Windasari; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The variables used in this study are the audit committee and external audit. The purpose of this study was to determine the effect of the audit committee and external audit on earnings management, to determine the effect of the audit committee on earnings management, and to determine the effect of external audit on earnings management. The population in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX). While the sample in this study are companies engaged in non-financial industries. The sampling technique used in this study is a method with a purposive sampling approach. The data collection method used in this research is the documentation method because the data is in the form of secondary data. The data analysis method used in this study uses correlation and regression analysis methods to analyze the relationship and influence between variables in inferencial statistics. The results of this study are that the audit committee variable (X1) and external audit (X2) jointly affect earnings management, the audit committee (X1) has no significant effect on earnings management performance and external audit (X2) has a significant effect on earnings management.Keywords: Audit committee, external audit and Earnings Management